Implementasi program bina pribadi Islami dalam membentuk akhlak santri Madrasah Aliyah Pesantren Al -Ihsan Boarding School Riau - Mahendra, Yasril Ihza; Alpizar, Alpizar (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
The moral decadence of students, Madrasah Aliyah Pesantren Al Ihsan Boarding School Riau, located in Kubang Jaya, has realized and anticipated this by implementing moral education to its students through the Islamic Personal Development program. This study was analyzed descriptively analytical. The results of the study indicate that (1) The implementation of the Islamic Personal Development (BPI) program at Madrasah Aliyah Pesantren Al Ihsan Boarding School Riau consists of programs, namely regular and non-regular programs. The regular program is the BPI weekly meeting held every Friday. While the non-regular program is the BPI outing class which is sometimes carried out in the form of cooking, sports, and overnight stays. (2) The supporting factors for the implementation of the BPI program are complete facilities and infrastructure, BPI mentor teachers have good Islamic knowledge competence, the BPI Deputy is specially formed, and the enthusiasm of most students. Meanwhile, the inhibiting factors for the BPI program are the following two things: (1) There are still students who are not active in participating in the BPI program, and (2) The limited duration provided by the school in implementing the routine meetings every Friday, where the duration given by the school for each meeting is only around one hour.